Implementasi Pendekatan Teaching at the Right Level (TaRL) melalui Pembelajaran Berdiferensiasi untuk Siswa SD Kelas II - 'Adawiyyah, Robi'atul; Agustini, Ferina; Sari, Ratna Nina (AS-SABIQUN, 2024)
The diverse learning needs and understanding levels of students require teachers to be creative in crafting learning experiences. The realization of student-centered and empowering learning is one solution to the diverse needs and levels of understanding of students. Differentiated learning is a learning effort based on the needs, characteristics and learning styles of learners. Learning by implementing the Teaching at The Right Level approach can accommodate the learning needs of diverse students. This study aims to provide an overview of the implementation of the Teaching at The Right Level (TaRL) approach in differentiated learning in grade II of SD Negeri Kalicari 01. The research methodology used is descriptive qualitative. The data sources used are the implementation of learning itself and field notes obtained during the research. Data collection techniques include interviews, observations, and document analysis. The results of the study show that the application of the TaRL approach in differentiated learning can be done by grouping students based on their level of understanding, designing learning plans, and implementing learning according to the plan that has been prepared. Differentiated learning with the TaRL approach is a positive good practice because it can accommodate the needs and skills of students in grade II SD Negeri Kalicari 01.